BRIDGING CRITICAL DISCOURSE ANALYSIS IN MEDIA DISCOURSE STUDIES - Ratna Sari; Silvia Eka Putri; Herdi Herdi; Budianto Hamuddin (University of Kuningan, 2018)
The precarious and critical period of the initiation of Discourse Analysis was populer at the end of the 1990s and the beginning of 2000s. Various approaches and frameworks were proposed during the time especially in the field of Applied Linguistics. This is including Critical Discourse Analysis (CDA) as one of its leading areas.Â This present study aimed at exploring and catching out how the CDAâ€™ presentation in overall related to Media studies and how it can be applicable to uncover an unseen ideologies while examining the existence of media discourse studies. The study is considering 25 journal studies to scrutinize the ways and methods used in discern social phenomena while illuminating the true characteristics of the social actors. As result, it was revealed thatÂ CDA is used openly to expose ideologies that somehow differentiate oppressed groups by offering a dummy image used by the highest authority or elite.Keywords: CDA; ideology; media discourse; social actors; power.